2014
DOI: 10.1002/tox.22090
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol a exposure promotes the migration of NCM460 cells via estrogen receptor‐mediated integrin β1/MMP‐9 pathway

Abstract: Bisphenol A (BPA) is a widely used industrial chemical and also an environmental endocrine disruptor (EED), which serves as a monomer in the manufacture of polycarbonate plastics. BPA enters human body mainly through oral intake, and has been reported as being linked to oncogenesis in many tissues. However, the association of BPA intake with gastrointestinal cancer, such as colon cancer, has received less attention. The present study was conducted to investigate the effects of BPA on the migration of normal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 37 publications
0
15
1
5
Order By: Relevance
“…Our present study revealed that BPA can trigger the in vitro cell motility of TNBC cells, which is consistent with recent data that BPA can stimulate the cell migration in some hormone‐dependent or hormone‐independent cancers . Furthermore, our study indicated that nanomolar BPA can increase the expression and transcription of MMP‐2 and MMP‐9 in TNBC cells in a time‐dependent manner.…”
Section: Discussioncontrasting
confidence: 41%
See 1 more Smart Citation
“…Our present study revealed that BPA can trigger the in vitro cell motility of TNBC cells, which is consistent with recent data that BPA can stimulate the cell migration in some hormone‐dependent or hormone‐independent cancers . Furthermore, our study indicated that nanomolar BPA can increase the expression and transcription of MMP‐2 and MMP‐9 in TNBC cells in a time‐dependent manner.…”
Section: Discussioncontrasting
confidence: 41%
“…Our results that BPA can up‐regulate the expression of MMP‐2 and MMP‐9 in TNBC cells are consistent with recent data observed in ovarian and lung cancer cells. Other studies also demonstrated that BPA stimulates MMP‐9 secretion by human granulosa lutein cells and normal colon epithelial cells (NCM460 cells) . BPA can also increase the expression of Vim and FN in colorectal and cervical cancer cells but not in the present study by the use of MDA‐MB‐231 or BT‐549 cells.…”
Section: Discussionmentioning
confidence: 99%
“…21,25 Furthermore, BPA treatment can also increase the expression of matrix metalloproteinases in cancer cells. 10,21,26 The effects of BPA on the expression and activation of these signal molecules required further studies.…”
Section: Discussionmentioning
confidence: 99%
“…La senescencia del endotelio tras la exposición al BPA se tradujo en un empeoramiento de la capacidad de reparar una herida en la monocapa de células. Algunos estudios [35] realizaron ensayos de herida en células epiteliales de mucosa de colon NCM460, mostrando que a dosis similares a las nuestras no se inducía la reparación de la herida, sin embargo, en fibroblastos cardiacos con otras concentraciones más altas (10 M) y en tratamientos a 24 y 48 horas se encontró el efecto contrario [36]. Hay que resaltar que los tratamientos es estos estudios son modelos agudos y el nuestro es un modelo de exposición a cinco días por lo que no son totalmente comparables.…”
Section: Discussionunclassified